Analysis of Factors Affecting the Motivation of Elderly to Follow the Covid-19 Vaccine in Bedoro Sragen Village - Tri Susilowati; Erika Dewi Noorratri (STIKes Patria Husada Blitar, 2023)
The COVID-19 disease caused by the SARS-CoV 2 virus has worried the world. WHO (World Health Organization) declared Covid-19 a pandemic so that WHO implemented a world health emergency status. More than 800 thousand people in Indonesia have been infected with COVID 19 and the number who have died was over 25 thousand people. Central Java provincial government data showed that the number of positive confirmed cases of Covid-19 in Sragen Regency was 2,694. Data compiled from the Sragen District Health Office, there were 775,774 vaccination targets in the Sragen area, including 118,893 elderly people. As for the elderly target group, 49,987 people or 42.01% have been successfully vaccinated. To analyze the factors that influence the motivation of the elderly in participating in the Covid-19 vaccine in the Bedoro Subdistrict, Sambungmacan, Sragen. The method used in this research was an analytic survey with a cross sectional approach. The results showed that most of the respondents' education level was in the basic education category, namely 67 (50.4%). Most of the respondents' knowledge was in the sufficient knowledge category, namely 113 (85%). Most of the respondents' perceptions were in the category of sufficient perception, namely 114 (85.7%). Most of the family support was in the adequate family support category, namely 112 (84.2%). Most of the motivation was in the category of moderate motivation, namely 111 (83.5%). The factor that most influences the elderly to take the COVID 19 vaccination was family support ((Exp(B): 2,488). Family support was the factor that most influences the elderly to take the COVID 19 vaccination